Pore-scale conjugate heat transfer simulations using lattice Boltzmann methods for industrial applications. (5th January 2021) - Ross-Jones, Jesse; Gaedtke, Maximilian; Sonnick, Sebastian; Meier, Manuel; Rädle, Matthias; Nirschl, Hermann; Krause, Mathias J.
Highlights: Heat transfer is estimated through procedurally generated micro porous silica. Internal vacuum pressures, 10 mBar to 1 Bar, are numerically evaluated. Local pore size is evaluated to numerically simulate pore scale heat transfer. Automated numerical approach studies thermal conductivity from particle measurements. The numerical simulation results are compared to literature and measure ment values. Abstract: Best practice energy efficiency goals (EU 2030 climate & energy framework) require substantial improvements in thermal insulation. Vacuum Insulation Panels (VIPs) offer considerable advantages over traditional insulation materials in terms of thermal insulation performance, with effective thermal conductivities between 0.004 and 0.008 W/(m · K) (Kalnæs and Jelle, 2014). Each application, however, has different requirements, and the influence of the VIPs' microstructure on the insulation performance is not yet entirely understood. Thus, in this work, a methodology is presented to achieve a complete pathway from measured particle characteristics to the resulting macroscopic heat transfer. The authors use the primary particle size, primary pore size, aggregate diameter, shape and standard deviation, as well as overall packing porosity to define a mesoscopic procedural generation of nano-porous geometry. Moreover, the local pore size is evaluated in order to simulate pore scale heat transfer. A distinct advantage over similar methods is the holistic approach presented provides direct tuning and control over particle packing characteristics to study their influence on conduction and radiation independently. The proposed automated numerical approach is applied to study the effective thermal conductivity of silica samples directly from particle measurements, enabling rapid prototyping of packing materials for varied compositions, facilitating the production of application optimized VIP configurations. The simulation results are compared to measurement and literature values.